Effect of nitrogen-starvation on growth pattern and expression of nitrogen assimilation genes - YADAVA, PRANJAL; AGGARWAL, CHETANA; VERMA, RACHANA; KUMAR, KRISHAN; SINGH, ISHWAR (The Indian Journal of Agricultural Sciences, 2020)
Studying plant response and adaptation under low nitrogen stress condition is pre-requisite to enhance nitrogen use efficiency in crops. The present study investigated the physiological and molecular responses of maize (Zea mays L.) to nitrogen stress during early vegetative stage. Maize seedlings were grown hydroponically under controlled environmental conditions in phytotron. One set of plants were nutritionally stressed by eliminating nitrogen source in hydroponic culture while the other set was provided with nitrogen (2 mM KNO3). Under nitrogen-starvation condition, plant growth and physiological parameters changed dramatically. Significant reduction in chlorophyll content, total soluble proteins and nitrate reductase activity was observed. Further, nitrogen-starvation resulted into differential expression of genes related to nitrogen-assimilation and metabolism. The present study might be useful to improve our understanding towards plants adaptive response under nitrogen-starvation conditions.